Lavi the United States, Israel, and a controversial fighter jet - Golan, John W. (Potomac Books, an imprint of the University of Nebraska Press, 2016)
he Lavi fighter program, the largest weapons-development effort ever undertaken by the State of Israel, envisioned a new generation of high-performance aircraft. In a controversial strategy, Israel Aircraft Industries intended to develop and manufacture the fighters in Israel with American financial support. The sophisticated planes, developed in the mid-1980s, were unique in design and intended to make up the majority of the Israeli air force. Though considerable prestige and money were at stake, developmental costs increased and doubts arose as to whether the Lavi could indeed be the warplane it was meant to be. Eventually the program became a microcosm for the ambitions, fears, and internal divisions that shaped both the U.S.-Israeli relationship and Israeli society itself. But the fighter never made it to operational service, and until now, the full breadth and significance of the Lavi story have never been examined and presented